Analysis on loan procedures between Islamic banking and conventional banking at Koperasi Permodalan Felda Berhad (KPF) / Nur Fadillah Hassan Basri - Hassan Basri, Nur Fadillah (2010)
The Shariah compliance with principles is an integral feature in the Islamic banking and finance. Shariah deliberation and interpretation process is imperative in assuring such compliance. Harmonisation of Shariah interpretations will underpin a comprehensive and wholesome development of this sector. It will strengthen the regulatory and supervisory oversight of the industry and will also foster and nurture a pool of competent Shariah ad-visers. Among initiative to achieve the above objectives, Bank Negara Malaysia has amended the Central Bank of Malaysia Act 1958 to enhance the role and functions of its Shariah Advisory Council of Bank Negara Malaysia (SAC). This amendment has accorded the SAC as the sole Shariah authority in Islamic finance. The common Shariah concepts adopted in Islamic finance is Wadiah, Qardh, Mudhara-bah and others. However, since there is a need to address the contemporary issues and subscribe to the majority opinion of Shariah scholars, the Tawarruq concept is now intro-duced. Most cooperatives in Malaysia are using the Islamic concept as the basis of guid-ance in their business. Even though the concept has long been discussed by the Shariah scholars, only recently such concept was being practically implemented. This concept is regarded as an alternative to Bai’Inah concept and is used in product financing, deposits and financial liquidity management.